From Letters to Vlog Entries: Truthfulness as a Literary Trope in Fictional Life Writing - Ackermans, Hannah (FRAME, Journal of Literary Studies, 2026)
This article proposes that the vlog adaptation is a remediation of the epistolary novel by examining the logic of immediacy. Although immediacy is often approached as a mediumspecific characteristic of digital media, this article illustrates that both the epistolary novel and the vlog adaptation implement narrative characteristics of non-fictional genres to create an experience of immediacy. This experience of immediacy is taken to the next level by the vlog adaptation, in which the narrative’s serialization creates a temporal experience parallel to the viewer’s temporal experience. The truthfulness associated with life writing thus becomes a literary trope in fiction.